Correction: Extended visible to near-infrared harvesting of earth-abundant FeS2–TiO2 heterostructures for highly active photocatalytic hydrogen evolution. Issue 11 (3rd May 2018) - Kuo, Tsung-Rong; Liao, Hsiang-Ju; Chen, Yu-Ting; Wei, Chuan-Yu; Chang, Chia-Che; Chen, Yi-Chia; Chang, Yi-Hsuan; Lin, Jou-Chun; Lee, Yi-Cheng; Wen, Cheng-Yen; Li, Shao-Sian; Lin, Kung-Hsuan; et al.
Abstract : Correction for 'Extended visible to near-infrared harvesting of earth-abundant FeS2 –TiO2 heterostructures for highly active photocatalytic hydrogen evolution' by Tsung-Rong Kuo et al., Green Chem., 2018, 20, 1640–1647.